2012
DOI: 10.2298/hemind111122007t
|View full text |Cite
|
Sign up to set email alerts
|

Effects of operating parameters on efficiency of lead removal by complexation-microfiltration process

Abstract: Majority of lead content found in the environment is the result of human activities. Heavy metals can be hazardous because they tend to bioaccumulate. Complexation-microfiltration process for the removal of Pb(II) ions was studied. The aim of microfiltration of the model wastewater containing heavy metal ions was finding an optimum ratio between the concentrations of the complexing agent and metal, and determining the most favorable pH value. The microfiltration experiments were carried out in a stirred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Lead, which is widely used as an industrial raw material for battery manufacturing, acid metal plating and nishing, ammunition, tetraethyl lead manufacturing, ceramic and glass industries printing, and the painting and dying industry, 1,2 has been considered as one of the most toxic contaminants discharged into the environment requiring urgent and intensive monitoring and strong policies. 3 It is reported that lead is nonbiodegradable and toxic to human beings, especially children.…”
Section: Introductionmentioning
confidence: 99%
“…Lead, which is widely used as an industrial raw material for battery manufacturing, acid metal plating and nishing, ammunition, tetraethyl lead manufacturing, ceramic and glass industries printing, and the painting and dying industry, 1,2 has been considered as one of the most toxic contaminants discharged into the environment requiring urgent and intensive monitoring and strong policies. 3 It is reported that lead is nonbiodegradable and toxic to human beings, especially children.…”
Section: Introductionmentioning
confidence: 99%
“…The available literature in this area is mainly based on the study of the chalcopyrite behavior [14][15][16], while the enargite characteristics have not been widely investigated. Recently, research aims have been directed to determining the influence of different leaching media on the arsenic utilization from copper ores and concentrates [2,4,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Arsenic In Complex Copper Concentratesmentioning
confidence: 99%